2014
DOI: 10.1001/jamadermatol.2013.7124
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Tanning Among High School Students in the United States, 2009 and 2011

Abstract: IMPORTANCE Indoor tanning is associated with an increased risk of skin cancer, including melanoma, and is particularly dangerous for younger and more frequent indoor tanners. OBJECTIVE To examine the prevalence of indoor tanning and frequent indoor tanning (≥10 times during the 12 months before each survey) and their association with health-related behaviors. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study examined data from the 2009 and 2011 national Youth Risk Behavior Surveys, which used natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
93
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 44 publications
7
93
0
6
Order By: Relevance
“…A meta-analysis of 88 studies from Western countries found the prevalence of ever exposure to indoor tanning to be 55 % for all university students and 19 % for all adolescents, with female university students (69 %) and adolescents (32 %) tanning at a higher prevalence than males (40 and 14 %, respectively) [3]. Further, surveys of American high school students reveal that tanning bed use is a frequent behavior, with 54 % of female and 41 % of male tanners using a tanning bed ten or more times in the past year [4]. These high rates of tanning bed use contribute to a substantial number of skin cancer cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 88 studies from Western countries found the prevalence of ever exposure to indoor tanning to be 55 % for all university students and 19 % for all adolescents, with female university students (69 %) and adolescents (32 %) tanning at a higher prevalence than males (40 and 14 %, respectively) [3]. Further, surveys of American high school students reveal that tanning bed use is a frequent behavior, with 54 % of female and 41 % of male tanners using a tanning bed ten or more times in the past year [4]. These high rates of tanning bed use contribute to a substantial number of skin cancer cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…The NSS2 also found that indoor tanning is more common among females, particularly young women, a finding echoed by research conducted elsewhere. [12][13][14][15][16][17][18][19][20][21][22] Fewer studies, however, have explored the sex differences in behaviours to do with indoor tanning. [16][17][18]21,24 Robust crosssectional and longitudinal surveys about indoor tanning behaviours are rare, no less so than in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…25 Indoor tanning is also correlated with smoking and susceptibility to smoking, binge drinking and drug use. 12,13,16,18,[20][21][22]24,26 It may be that adolescents who tan indoors are more susceptible to engage in risk behaviours despite the risks being well documented. The association between indoor tanning and risk behaviours that are unrelated to appearance enhancement suggests that some engage in these behaviours for other purposes, such as to cope with anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations